2015
DOI: 10.1136/heartjnl-2015-307550
|View full text |Cite
|
Sign up to set email alerts
|

Atrial flutter and thromboembolic risk: a systematic review

Abstract: Atrial flutter confers a thromboembolic risk, but contrary to atrial fibrillation the relationship has only been addressed in few studies. This study performs an up to date systematic review of the literature to investigate the association between atrial flutter and thromboembolic events. Articles were found by MEDLINE, EMBASE search and a manual search of references list in included articles. International guidelines, meta-analyses, reviews, case reports, studies reporting thromboembolic events in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 60 publications
0
34
0
9
Order By: Relevance
“…Dostępne dowody wskazują, że ryzyko udaru mózgu u pacjentów z trzepotaniem przedsionków nie różni się bardzo od ryzyka w przypadku AF [827]. Co więcej, u wielu pacjentów, u których rozpoznaje się trzepotanie przedsionków, później pojawia się AF [993][994][995].…”
Section: Postępowanie W Trzepotaniuunclassified
“…Dostępne dowody wskazują, że ryzyko udaru mózgu u pacjentów z trzepotaniem przedsionków nie różni się bardzo od ryzyka w przypadku AF [827]. Co więcej, u wielu pacjentów, u których rozpoznaje się trzepotanie przedsionków, później pojawia się AF [993][994][995].…”
Section: Postępowanie W Trzepotaniuunclassified
“…A recent systematic review of the literature on atrial flutter and thromboembolic risk concluded that while a risk certainly exists, the exact estimate is challenging. 44 There have not been any randomized controlled trials examining this association, and atrial flutter often coexists with AF and likely derives from a common pathophysiological mechanism. Although atrial flutter is not mentioned in guidelines for the primary prevention of stroke, guidelines on the secondary prevention of stroke recommend that similar treatment parameters should be followed for atrial flutter as for AF.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…The same recommendation applies to patients with atrial fibrillation, who can be assumed to have a comparably high risk of thrombembolism [52]. In addition to the vitamin K antagonists, 4 preparations are currently available from the group of non-vitamin K antagonist anticoagulants (NOAC) (▶ table 4), including the direct thrombin inhibitor dabigatran as well as 3 factor Xa antagonists (rivaroxaban, apixaban, edoxaban).…”
Section: Antithrombotic Therapymentioning
confidence: 99%